2019
DOI: 10.1101/782243
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanosensitive regulation of FGFR1 through the MRTF-SRF pathway

Abstract: Controlling basic fibroblast growth factor (bFGF) signaling is important for both tissueengineering purposes, controlling proliferation and differentiation potential, and for cancer biology, influencing tumor progression and metastasis. Here, we observed that human mesenchymal stromal cells (hMSCs) no longer responded to soluble or covalently bound bFGF when cultured on microfibrillar substrates, while fibroblasts did. This correlated with a downregulation of FGF receptor 1 (FGFR1) expression of hMSCs on micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…On top of 2D gels, many large focal adhesions formed, but when a gel was pipetted on top of MSCs attached to 2D gels, or when cells were embedded in 3D hydrogels, only few and small focal adhesions were observed. We have recently shown a similar decrease of focal adhesions in stiff 3D electrospun and additive manufactured scaffolds, compared to 2D films of the same stiff material [118,119] . Rather than forming large protein complexes that tightly anchor the cell to the 2D substrate, the focal adhesion proteins are distributed more diffusely through the cell and regulate protrusion activity and matrix deformation [115,120] .…”
Section: Focal Adhesionsmentioning
confidence: 65%
See 1 more Smart Citation
“…On top of 2D gels, many large focal adhesions formed, but when a gel was pipetted on top of MSCs attached to 2D gels, or when cells were embedded in 3D hydrogels, only few and small focal adhesions were observed. We have recently shown a similar decrease of focal adhesions in stiff 3D electrospun and additive manufactured scaffolds, compared to 2D films of the same stiff material [118,119] . Rather than forming large protein complexes that tightly anchor the cell to the 2D substrate, the focal adhesion proteins are distributed more diffusely through the cell and regulate protrusion activity and matrix deformation [115,120] .…”
Section: Focal Adhesionsmentioning
confidence: 65%
“…However, the MRTF/SRF pathway has not yet been investigated 3D MSC differentiation in tissue-engineering constructs. We have recently shown that the MRTF/SRF pathway influences proliferation of MSCs in 3D ESP scaffolds through the regulation of FGFR1 [119] . Given the profound effects of MRTF/SRF on 2D MSC differentiation, investigating their role in a 3D setting would be highly interesting.…”
Section: Mrtf/srfmentioning
confidence: 99%